Ex-Dividend Day Share Price Behavior: Effects of the Tax Reform Act of 1986 - Lamdin, Douglas J.; Hiemstra, Craig (The Review of Economics and Statistics, 1993)
The authors examine ex-dividend day share price behavior in light of the Tax Reform Act of 1986. Data from 1982 through 1991 are examined. The evidence generally supports the traditional view that differential taxation does affect the valuation of dividends and capital gains rather than the tax irrelevance view that it does not. Copyright 1993 by MIT Press.